Efficient use of a limited resource: A comparison of femoral head allograft preparation methods. (26th September 2017) - Marshall, Timothy; Chow, Jason; Sivakumar, Brahman; Ahmed, Nushin; Smith, Paul
Purpose: The purpose of the study was to compare the yield and compressed volume of femoral head allograft prepared by either hand morselization or a bone mill. Methods: Twenty human femoral head allografts were donated from a bone bank and morselized by two different methods. The heads were divided in half and split into two sample groups. One group underwent hand morselization with large bone nibblers, while the other was prepared using a bone mill. The volume of graft produced was measured. Ten-gram aliquots of each sample then underwent 30 impactions in a contained cavity, with the volume of graft compression measured. Results: Bone milling yielded approximately 31% more usable graft than hand morselization (81% to 50%; p = 0.0001). There was no difference between the compressed volume of graft prepared by either method ( p = 0.14). Conclusion: This study demonstrates the efficacy of preparation of allograft with a bone mill and assists the clinician in determining the yield of graft by the weight of femoral head, thereby potentially minimizing excessive ordering and wastage.